Reduced T Cell and Antibody Responses to Inactivated Coronavirus Vaccine Among Individuals Above 55 Years Old - Medeiros, Giuliana X.; Sasahara, Greyce Luri; Magawa, Jhosiene Y.; Nunes, João Paulo S.; Bruno, Fernanda R.; Kuramoto, Andreia C.; Almeida, Rafael R.; Ferreira, Marcelo A.; Scagion, Guilherme P.; Candido, Érika D.; Leal, Fabyano B.; Oliveira, Danielle B. L.; et al. (Frontiers in Immunology, 2022)
CoronaVac is an inactivated SARS-CoV-2 vaccine that has been rolled out in several low and middle-income countries including Brazil, where it was the mainstay of the first wave of immunization of healthcare workers and the elderly population. We aimed to assess the T cell and antibody responses of vaccinated individuals as compared to convalescent patients. We detected IgG against SARS-CoV-2 antigens, neutralizing antibodies against the reference Wuhan SARS-CoV-2 strain and used SARS-CoV-2 peptides to detect IFN-g and IL-2 specific T cell responses in a group of CoronaVac vaccinated individuals (N = 101) and convalescent (N = 72) individuals. The frequency among vaccinated individuals, of whom 96% displayed T cell and/or antibody responses to SARS-CoV-2, is comparable to 98.5% responses of convalescent individuals. We observed that among vaccinated individuals, men and individuals 55 years or older developed significantly lower anti-RBD, anti-NP and neutralization titers against the Wuhan strain and antigen-induced IL-2 production by T cells. Neutralizing antibody responses for Gamma variant were even lower than for the Wuhan strain. Even though some studies indicated CoronaVac helped reduce mortality among elderly people, considering the appearance of novel variants of concern, CoronaVac vaccinated individuals above 55 years old are likely to benefit from a heterologous third dose/booster vaccine to increase immune response and likely protection.